Development of Tourism in a Secondary City on The Andaman Sea Coast - Praphan, Anusorn (The Journal of Development Administration Research, 2025)
This research aims to study concepts, 1)To study the tourism conditions of the secondary cities on the Andaman coastal cities. 2)To study the factors that are important for the development of tourism in the Andaman coastal cities. 3)To study the guidelines for developing tourism in the Andaman coastal cities. It is qualitative research that collects data by studying document. In-depth interviews and focus group discussions with key informant, including: Personnel of government agencies, personnel in the private sector and the public sector Experts and academics involved in implementing tourism policies in secondary cities. The results of the research found that. 1) Information on the condition of tourist areas in the secondary cities on the Andaman coast. There are a small number of tourists due to many factors. The condition of the urban area on the Andaman coast is because it is a remote area from the city. Travelers must travel by car and boat to reach tourist attractions. The infrastructure such as roads, electricity, and tap water are not up to standard, including inadequate budget allocation in some areas, which is an obstacle to tourism. The connectivity city areas when the main city is overcrowded with tourists can develop secondary city tourist attractions which are adjacent to each other in some provinces to be at the same level or similar to the main city to accommodate the expected increase in tourists in the future. 2) Factors affecting development in the context of leadership need to be considered in conjunction with each other as secondary cities have unique characteristics that differ from primary cities such as limited resources, incomplete infrastructure and lower competitiveness. Public and private sector participation still lacks personnel with expertise in providing services to tourists. Problems with ineffective public and private sector participation affect the growth of the tourism industry in secondary cities in the Andaman coastal area. Cooperation between the public and local leaders lacks continuous communication in order to effectively and efficiently follow up on various operations. 3) Guidelines for developing tourism in the Andaman coastal cities by developing infrastructure, integrating attractions, transportation, convenience and safety, and public utilities, developing drinking water sources, electricity and telecommunications in tourist attractions to meet standards. Standard facilities and services, community participation of natural resources, including the preservation of culture and traditions, creating a balance between development and conservation of nature, effective collaboration between government personnel, citizens, and entrepreneurs, and publicizing tourist attractions can promote sustainable tourism in secondary cities on the Andaman coast.